P254 Crohn's disease of the pouch: an overdiagnosed condition?. (21st January 2022) - de Jong, D C; Reijntjes, M; Wessels, E; Buskens, C; Hompes, R; Löwenberg, M; Gecse, K; D'Haens, G; Bemelman, W; Duijvestein, M
Abstract: Background: Approximately 10% of ulcerative colitis (UC) patients undergoing ileal pouch-anal anastomosis (IPAA) are believed to develop ' de novo Crohn's disease' (CD) of the pouch (1). Clear diagnostic criteria are lacking, but the diagnosis is mostly based on the development of fistula, strictures, treatment refractory disease, pre-pouch ileitis, or typical endoscopic findings fitting with CD, such as ulcers and patchy inflammation (1, 2). However, the findings on which this diagnosis is established may be caused by (unrecognized) surgical complications such as silent anastomotic leakage. It is important to distinguish these complications from what is truly a ' de novo CD' as treatment strategies differ in both groups. We aimed to investigate incidence rates and reasons for diagnosing CD of the pouch. Methods: In total, 483 consecutive UC patients who underwent a proctocolectomy and IPAA in a tertiary IBD referral centre from January 1990 until December 2017 were retrospectively reviewed. Patients with a diagnosis 'CD of the pouch' were identified based on medical records, and could be based on either clinical, endoscopic, imaging and/or histological findings. Results: Median follow-up time was 20 years (IQR 10 – 24). In 46 out of 483 patients (10%), de novo CD of the pouch was diagnosed, which was mostly based on endoscopic findings (29/46, 63%). Presence of pre-pouch ileitis was the most common reason to diagnose CD of the pouch, which was present in 18/29 patients (62%), followed by ulcerations in 6/29 (21%). On MRE, 19/46 (41%) patients had a fistula or sinus, 4/46 patients (9%) had a stricture (all proximal of the pouch). Interestingly, 12/46 patients (26%) never underwent cross sectional imaging after IPAA construction. Only ten patients (22%) showed histologic findings with a preference for CD in biopsies, revised colectomy specimen, and/or pouch excision specimen. Only two patients had granulomas, others showed signs of transmural inflammation, ulcerations or fibrosis. Other histologic findings were non-specific. Conclusion: In our centre, 10% of patients were 'diagnosed' with de novo CD of the pouch. However, as confirmatory histological signs of CD were present in only 22%, chronic surgical complications as underlying cause might be of greater importance. It is advised to perform cross sectional imaging in every patient after a year after pouch construction to rule out silent leaks that might cause symptoms at a later stage mimicking Crohn's disease, avoiding a diagnostic dilemma.